Hypothalamus Specific Re‐Introduction of SNORD116 into Otherwise Snord116 Deficient Mice Increased Energy Expenditure. (22nd October 2017) - Qi, Y.; Purtell, L.; Fu, M.; Zhang, L.; Zolotukhin, S.; Campbell, L.; Herzog, H.
Abstract : The Snord116 gene cluster has been recognised as a critical contributor to the Prader–Willi syndrome (PWS), with mice lacking Snord116 displaying many classical PWS phenotypes, including low postnatal body weight, reduced bone mass and increased food intake. However, these mice do not develop obesity as a result of increased energy expenditure. To understand the physiological function of SNORD116 better and potentially rescue the altered metabolism of Snord116 −/− mice, we used an adeno‐associated viral (AAV) approach to reintroduce the product of the Snord116 gene into the hypothalamus in Snord116 −/− mice at different ages. The results obtained show that mid‐hypothalamic re‐introduction of SNORD116 in 6‐week‐old Snord116 −/− mice leads to significantly reduced body weight and weight gain, which is associated with elevated energy expenditure. Importantly, when the intervention targets other areas such as the anterior region of the hypothalamus or the reintroduction occurs in older mice, the positive effects on energy expenditure are diminished. These data indicate that the metabolic symptoms of PWS develop gradually and the Snord116 gene plays a critical role during this process. Furthermore, when we investigated the consequences of SNORD116 re‐introduction under conditions of thermoneutrality where the mild cold stress influences are avoided, we also observed a significant increase in energy expenditure. In conclusion, the rescue of mid‐hypothalamic Snord116 deficiency in young Snord116 germline deletion mice increases energy expenditure, providing fundamental information contributing to potential virus‐mediated genetic therapy in PWS.